LANGUAGE LEARNING BELIEFS OF INDONESIAN ENGLISH EDUCATION STUDY PROGRAM STUDENTS - Amrullah, Amrullah; Vianty, Machdalena; Fiftinova, Fiftinova (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2018)
Abstract: This study aimed to investigate students? beliefs about language learning. BALLI (Beliefs About Language Learning Inventory) was administered to a total of seventy five first year students of English Education Study Program, Faculty of Teacher Training and Education within Sriwijaya university in South Sumatera, Indonesia. The findings showed that  among the five categories of BALLI, the beliefs associated with motivation were the strongest, while those associated with the difficulty of language learning are the weakest. The findings also support significant difference in motivation associated with gender. Key words: language learning beliefs, motivation, Indonesian college students